Investigation of short- and long-term effects of ovarian hyperstimulation syndrome on ovarian reserve: an experimental study - Pala, S.; Affigan, R.; Ozkan, Z. S.; Akpolat, N.; Ilhan, N.; Sapmaz, E. (I R O G Canada, Inc, 2015)
Purpose: To investigate the short and long term effects of ovarian hyperstimulation syndrome (OHSS) on serum levels of vascular endothelial growth factor (VEGF) and endothelin-1 and ovarian follicular reserve (OFR). Materials and Methods: An experimental case-control study was conducted on a university animal laboratory with 20 immature (22-day-old) virgin female Wistar Albino rats. Firstly, rats were divided into two groups. Group 1 (n = 10): control and Group 2 (n = 10): experimental OHSS induced rats. Secondly, Group 2 was randomly divided into two groups on the day of OHSS development (271 day) as follows: Group 3 (n = 5): 27-day-old OHSS induced rats and Group 4 (n = 5): 27-day-old OHSS induced rats supervised for seven days. Group 1 was divided into two groups to constitute age-matched controls as follows: Group 5 (n = 5): 27-day-old rats, Group 6 (n = 5): 35-day-old rats. The comparisons of Group 3 vs Group 5 and Group 4 vs Group 6 were performed. Main outcome measures were OFR, serum levels of VEGF, and endothelin-1. Results: While the OFR and primordial follicle number (PFN) of Group 3 were significantly lower than those of Group 5 (p < 0.05); VEGF and endothelin-1 levels and atretic follicle number (AFN) were significantly higher in Group 3 compared to Group 5 (p < 0.05). In Group 4, PFN was significantly lower (p < 0.05) and AFN was significantly (p < 0.05) higher than Group 6. However, there were no statistically significant difference between Group 4 and Group 6 regarding the parameters of OFR, serum levels of VEGF, and endothelin-1. Conclusion: This experimental OHSS model revealed increased serum VEGF and endothelin-1 levels and decreased OFR during short-term of OHSS. OHSS showed detrimental effect on PFN of rats during long-term.
Keywords: Endothelin-1; Ovarian follicle reserve; Ovarian hyperstimulation syndrome; VEGF